Adhesin RadD: the secret weapon of Fusobacterium nucleatum - Dingjiacheng Jia; Shujie Chen (Gut Microbes)
Fusobacterium nucleatum can promote colorectal cancer (CRC) development through a variety of virulence proteins. Zhang et al. recently identified an adhesin RadD, for Fusobacterium nucleatum adhesion to CRC. Targeting the interaction between RadD and CD147 will provide a new strategy for CRC treatment. This Commentary and View not only summarizes the research highlights but also discusses the possibility of targeted clearance of Fusobacterium nucleatum in clinical applications.